Development of novel adjustable focus head mount display for concurrent image-guided treatment applications. (31st October 2017) - Choi, Hojong; Ryu, Jaemyung; Yoon, Changhan
Abstract: Purpose: A conventional see-through head mount display contains many optical lenses, which can be problematic in image-guided treatment applications due to its size, weight, structure, and focus limitation. Therefore, we have designed a new type of see-through head mount display with a reduced number of optical lenses and an adequate optical resolution that can be utilized for image-guided treatment applications. Materials and methods: A new type of adjustable focus head mount display with expanded virtual images and an external treatment space that can be provided to the eyes of a user by enlarging the images of a small display is designed and investigated in this study. This type of head mount display can be used in image-guided treatment applications because of the dual paths of imaging and treatment from the optical systems. Therefore, this system with an adjustable focus function can aid doctors in obtaining images for the treatment of the eyes of patients because every patient has a unique pupil size. Results: The results of the adjustable focus see-through head mount display showed distortion values of +0.36% in the +1 diopter location and −0.55% in the −4 diopter location, and there are less significant modulation transfer function differences within the ±5 diopter locations. Conclusions: Low optical distortions within ±0.5 diopters can help doctors image the eye conditions of patients through fewer image processing techniques. Therefore, the designed adjustable focus head mount display can provide low optical aberrations and high optical modulation transfer function resolutions for image-guided treatment applications.